Ambientes informacionais digitais e usuários surdos: questões de acessibilidade - Corradi, Juliane Adne Mesa [UNESP] (2007)
The Information Science field, under the scope of technology of information and communication, has contributed to develop accessible interfaces that attend different user communities and their informational needs. In this direction, generation, treatment and dissemination processes of information must focus on the users and on the systems that allow the creation of adequate interfaces to the access and to the utilization of digital information contents. With emphasis on the bilingual perspective of deafness and also on Deaf Studies, this work aims to focus the digital and social inclusion processes of deaf users. These users use mainly the sign language in their informational and communicative interactions. Thus, this study presents the strongest points of information and communication technologies to build digital environments that include deaf users, emphasizing the possibility to promote digital accessibility to deafs under different sensorial, linguistic and motor conditions, especially Sign Language users ones. The research has an exploratory and descriptive approach, with literature revision and analysis of digital environments. Empirical data and the perception of the deaf users about accessibility were collected by means of questionnaires, in which their voices asked for better digital interfaces. Therefore, from the principles of Inclusive Digital Information Architecture, we developed a Model for Analysis and Development of Inclusive Digital Information Environments (MADAIDI), aiming to conduct the planning and implementation of inclusive digital information environments, with regard to peculiarities of diverse target publics, futhermost the deaf community. Researcher believes that the planning of an Inclusive Digital Information Architecture focused on universal design, usability, digital technologies and assistive technologies may allow the digital and social... (complete abstract click electronic access below)